Analysis of the Role of Oil and Gas Companies in Implementing the Achievements of SDGs 14 and 17 Through the Fish Cultivation Program in the Kepulauan Anambas District - Tambunan, Imran Gunawan; Sofilda, Eleonora (International Journal Labs, 2023)
Kepulauan Anambas District, with 98% of its territory consisting of waters, has promising fisheries potential, However, is inversely proportional to the performance achievement of the fisheries sector during the 2016-2020 period, which decreased. Nevertheless, overfishing continues to occur in Anambas waters. This study aims to analyze the role of oil and gas companies in efforts to develop aquaculture in Kepulauan Anambas District, the intended role focuses on how aquaculture practices are carried out, the involvement of fishing communities, also the benefits and challenges faced, this research method uses a mixed methods approach, by gathering information from relevant sources, both from the company side as program administrators, and fishermen groups as beneficiaries. The Information gathering was carried out qualitatively with in-depth interviews and quantitatively with questionnaires. The data was collected and analyzed by content analysis techniques and descriptive statistics related to the perceptions of fishermen groups towards sustainable fisheries by measuring using a Likert scale. The object of this research consists of entities of two oil and gas companies that have community development programs in the aquaculture sector, namely Medco E&P Natuna, Ltd and PT. Primer Oil BV-Harbour energy. The sample determined in this study consisted of 19 people divided into managers and company personnel in the CSR department, and cultivator community groups. The results of this study explain that through aquaculture, fishing companies make a positive contribution to the implementation of SDG number 14 concerning life below water, and number 17 concerning partnerships for the goals. Strategically, companies interpret these development goals by providing guidance in the form of investment, infrastructure, transfer of knowledge, technology, and management of aquaculture management which is carried out periodically, in particular, this research also identifies the forms of involvement of the two companies fostered groups, towards the achievements of the community development program, the results of this study also identified that only certain people have an interest in being involved Farther in management.